2017
DOI: 10.5194/acp-17-12779-2017
|View full text |Cite
|
Sign up to set email alerts
|

Do contemporary (1980–2015) emissions determine the elemental carbon deposition trend at Holtedahlfonna glacier, Svalbard?

Abstract: Abstract. The climate impact of black carbon (BC) is notably amplified in the Arctic by its deposition, which causes albedo decrease and subsequent earlier snow and ice spring melt. To comprehensively assess the climate impact of BC in the Arctic, information on both atmospheric BC concentrations and deposition is essential. Currently, Arctic BC deposition data are very scarce, while atmospheric BC concentrations have been shown to generally decrease since the 1990s. However, a 300-year Svalbard ice core showe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 61 publications
1
33
0
Order By: Relevance
“…Moore et al (2005) also confirmed that chemical stratigraphy remained preserved despite high melt ratios. More 5 recently, the impact of melting on the HDF ice core was assumed to be low compared to the EC deposition signal (Ruppel et al, 2014(Ruppel et al, , 2017. Similar findings were postulated for the Lomonosovfonna 2009 (LF-09) ice core in which melting impact was negligible on ionic species at a decadal resolution (Wendl et al, 2015).…”
supporting
confidence: 50%
See 2 more Smart Citations
“…Moore et al (2005) also confirmed that chemical stratigraphy remained preserved despite high melt ratios. More 5 recently, the impact of melting on the HDF ice core was assumed to be low compared to the EC deposition signal (Ruppel et al, 2014(Ruppel et al, , 2017. Similar findings were postulated for the Lomonosovfonna 2009 (LF-09) ice core in which melting impact was negligible on ionic species at a decadal resolution (Wendl et al, 2015).…”
supporting
confidence: 50%
“…However, EC concentrations in Svalbard snow (Aamaas et al, 2011;Doherty et al, 2010;Forsström et al, 2009Forsström et al, , 2013 as well as in the HDF and Fiescherhorn ice cores (Jenk et al, 2006;Ruppel et al, 2014Ruppel et al, , 2017 are one order of magnitude higher than rBC concentrations in the topmost part of the LF core. This can be mainly explained by the different analytical methods employed, which do not measure the same fraction of the carbonaceous compounds, as discussed by Ruppel et al (2014).…”
Section: High-resolution Rbc Recordmentioning
confidence: 98%
See 1 more Smart Citation
“…The entire LF-09 core and the LF-11 core were analyzed for rBC at PSI in several campaigns between 2012 and 2016 and in April-May 2016, respectively, following the proce-dure established by Wendl et al (2014) for liquid samples and further evaluated by Lim et al (2014). Discrete rBC samples were melted at room temperature, sonicated in a ultrasonic bath for 25 min, and immediately analyzed using a SP2 (Droplet Measurement Technologies, USA) (Schwarz et al, 2006;Stephens et al, 2003) coupled with a jet nebulizer (APEX-Q, Elemental Scientific Inc., USA). External calibrations from 0.1 to 50 ng g −1 (R 2 > 0.999) were usually performed twice a week by preparing eight fresh dilutions from a rBC standard (Aquadag ® , Acheson Industries Inc., USA) (Gysel et al, 2011;Wendl et al, 2014).…”
Section: Rbc Analysismentioning
confidence: 99%
“…Namely, in the case of atmospheric stability the BB particles can station at some height above ground where they can undergo aging effects while exerting a main action on the aerosol optical properties. At turbulent regimes, instead, the particles can more easily reach the ground and affect the albedo properties of snow and ice exposed surfaces even a long time after the BB transport event (Ruppel et al, 2017).…”
Section: Introductionmentioning
confidence: 99%